Polycarbazoles and polytriphenylamines showing aggregation-induced emission (AIE) and intramolecular charge transfer (ICT) behavior for the optical detection of nitroaromatic compounds. (12th October 2015) - Dong, Wenyue; Pina, Jõao; Pan, Yuyu; Preis, Eduard; Seixas de Melo, J. Sérgio; Scherf, Ullrich
Abstract: Acceptor-substituted polycarbazoles (PCzTPAN) and polytriphenylamines (PTPATPAN) bearing electron-deficient 2, 3, 3-triphenylacrylonitrile (TPAN) side groups have been successfully synthesized. Both of them are aggregation-induced emission (AIE)-active and show intramolecular charge transfer (ICT) behavior. PCzTPAN and PTPATPAN aggregates in 90% water/THF were used for the detection of 1, 3, 5-trinitrobenzene (TNB) as prototypical nitroaromatic compound. They show amplified PL quenching upon addition of TNB with a maximum quenching constant of 5.5 × 10 5 M −1 . As additional application example, the detection of the glass transition temperature of polystyrene (PS) was accomplished for PTPATPAN blended into PS at doping concentrations of 0.1–1.0 wt%. Graphical abstract: Polycarbazoles (PCzTPAN) or polytriphenylamines (PTPATPAN) decorated with 2, 3, 3-triphenylacrylonitrile side groups have been synthesized and characterized for the occurrence of aggregation-induced emission (AIE) and intramolecular charge transfer (ICT) effects. PCzTPAN and PTPATPAN dispersions in 90% water/THF were further used for the high sensitivity detection of 1, 3, 5-trinitrobenzene (TNB) as prototypical nitroaromatic analyte, showing amplified PL quenching with a maximum quenching constant of 5.5 × 10 5 M −1 . Moreover, PTPATPAN was used as AIE-active fluorescent probe for detection of the glass transition temperature of a polystyrene (PS) film, exhibiting a very reliable response to the glass transition of PS, up to low probe concentration of 0.1 wt%. Highlights: Acceptor-substituted polycarbazoles and polytriphenylamines showing both AIE and ICT behavior have been synthesized. Dispersions containing polymer aggregates have been used for optical detection of 1, 3, 5-trinitrobenzene. Amplified PL quenching was observed with a maximum PL quenching constant of 5.5 × 10 5 M −1 . One polymer (PTPATPAN) was used as PL-sensitive dopant in the Tg -detection of polystyrene.